THE QUALITY CHARACTERISTICS OF SOAP BY USE DIFFERENT SEAWEED - Afza, Muhammad Fakhran; Sumarto, Sumarto; Desmelati, Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis study aims to determine the quality characteristics of soap using seaweed. The research method was carried out experimentally by making soap from various types of seaweed. The research data were analyzed using a T-test analysis of soap made from 15 grams of E. cottonii, 10 grams of E. spinosum, and 15 grams of E. spinosum. The parameters analyzed were organoleptic (appearance, smell, texture), physical test (foam stability, pH), chemical analysis (moisture content, free alkalis, fatty acids, free fatty acids). Research shows that different use of seaweed affects the quality of the soap produced. The use of seaweed E. spinosum as much as 10 grams is the best treatment with the characteristics of soap, namely: it has a bright and clean appearance, fragrance, a hard texture, not sticky, 75.2% foam stability, pH 8.60, 21.86% moisture content, alkaline free 0.40%, 26.37% fatty acids and 0.68% free fatty acids. Keywords: Eucheuma cottonii, Eucheuma spinosum, soap